Overexpression of Aquaporin 1 in Synovium Aggravates Rat Collagen-Induced Arthritis Through Regulating β-Catenin Signaling: An in vivo and in vitro Study - Mu Y; Zhou M; Cai L; Liu M; Li R (Dove Medical Press, 2020)
Yu-rong Mu1,2 ,* Meng-yuan Zhou1,2 ,* Li Cai,3 Ming-ming Liu,1,2 Rong Li1,2 1School of Pharmacy, Anhui Medical University, Hefei, Anhui Province, People’s Republic of China; 2Inflammation and Immune Mediated Diseases Laboratory of Anhui Province, Hefei, People’s Republic of China; 3Department of Pathology, School of Basic Medicine, Anhui Medical University, Hefei, Anhui Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Rong LiSchool of Pharmacy, Anhui Medical University, Hefei, Anhui Province, People’s Republic of ChinaEmail aydlirong@163.comIntroduction: Previous studies have confirmed that aquaporin 1 (AQP1) is up-regulated in synovium of rheumatoid arthritis (RA), but its exact pathogenic mechanisms in RA are unclear. This study revealed the pathogenic role of AQP1 in rat collagen-induced arthritis (CIA) and the underlying mechanisms related to β-catenin signaling.Materials and Methods: Secondary paw swelling and pathological changes of ankle joints were used to evaluate the severity of rat CIA. Synovial AQP1 and β-catenin expression were measured by immunohistochemistry (IHC) and Western blot assay. AQP1 siRNA was applied to knockdown AQP1 in cultured CIA fibroblast-like synoviocyte (FLS). Assays of MTT, PCNA immunofluorescence and transwell were performed to detect cell proliferation, migration and invasion. The protein levels of β-catenin pathway members and ratio of TOP/FOP luciferase activity were also measured.Results: In vivo, we revealed that synovial AQP1 and β-catenin expressions in CIA rats were higher than normal rats, and synovial AQP1 expression of CIA rats increased in parallel with secondary paw swelling and total pathological score on joint damage. Correlation analysis of IHC results indicated that synovial AQP1 expression positively correlated with β-catenin expression in CIA rat. In vitro, AQP1 siRNA apparently reduced the proliferation, migration and invasion of CIA FLS by inhibiting β-catenin signaling pathway. As an activator of β-catenin signaling, lithium chloride (an inhibitor of GSK-3β) reversed the inhibitory effects of AQP1 siRNA on the cultured CIA FLS.Conclusion: We concluded that the overexpression of synovial AQP1 aggravated rat CIA by promoting the activation of FLS through β-catenin signaling pathway.Keywords: aquaporin 1, collagen-induced arthritis, fibroblast-like synoviocyte, rheumatoid arthritis, β-catenin signaling